The effect of teacher’s attitudes in supporting inclusive education by catering to diverse learners - Kazmi, Anjum Bano; Kamran, Mahwish; Siddiqui, Sohni (Frontiers in Education, 2023)
Several countries around the world, including Pakistan, are determined to achieve successful inclusion but are facing some major and minor challenges. For example, the dearth of physical and human resources and a lack of understanding, expertise, and attitudes. The present research was carried out to find out the role that teachers’ attitudes play in educating children suffering from behavioral disorders. Using the quantitative research design data were gathered from 230 randomly selected sample cases of teachers working in 10 traditional (non-inclusive) and 10 inclusive schools in Karachi, Pakistan. The teachers were asked to respond to items on the semantic differential scale and five-point Likert scale respectively to gauge their attitudes towards inclusive education. The analyses were carried out through Smart Partial Least Squares (Smart PLS) 3.0. The results from the Structural Equation Modeling analysis revealed that teachers have positive attitudes toward the education of children with behavioral disorders. Directly significant positive correlations indicated that teachers are prepared to cater students with mild behavioral disorders in their classrooms. The current study suggested the development of a support mechanism by the school administration and also the provision of guiding principles for increasing teachers’ self-efficacy to increase the chances of inclusion of students with behavioral disorders.